PELATIHAN PENGURUSAN JENAZAH DI DESA SEBANGUN - Suhari Suhari; Muspian Muspian (Jurnal Pengabdian Kepada Masyarakat, 2021)
This community service activity is in the form of managing corpses, which aims to provide knowledge and insight, especially on the procedures for managing corpses so that they can increase knowledge and practice of managing corpses in real terms in the community, especially in Sebagun Village. The target in this activity is the mosque's youth, totaling 30 people. The training was carried out using practical methods, lectures, and questions and answers. Community Service Activities can be carried out correctly and run smoothly following the activity plans that have been prepared, although not all participants have mastered the material presented well. This activity received an excellent response, as evidenced by the active participation of participants in the training until it was completed. This Community Service activity is to provide insight and knowledge to the youth of the Sebangun Village mosque. The training that has been carried out has been able to increase the knowledge of the trainees. Participants showed an attitude of curiosity about taking care of the corpse, so that the participants were enthusiastic in following it.